Statistics for Management and Economics, 12th Edition - Gerald Keller (Cengage Learning, 2022)
Discover how important statistical methods are for today's managers and economists as you learn how to apply these tools to real business problems with Keller's best-selling STATISTICS FOR MANAGEMENT AND ECONOMICS, 12E. This edition emphasizes applications over calculations. A unique three-step ""ICI"" approach to problem solving teaches you how to ""identify"" the correct statistical technique by focusing on the problem objective and data type; ""compute"" the statistics by hand or using Excel, XLSTAT or Stata; and, finally, ""interpret"" the results within the context of the problem. Data-driven examples and more than 30 updated cases demonstrate how marketing managers, financial analysts, accountants and economists rely on statistical applications. In addition, thousands of exercises and datasets use actual interesting, recent data from individuals, sports teams or even stock returns to let you practice what you've learned. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.